Electroconvulsive Therapy Hasn't Negative Effects on Short-Term Memory Function, as Assessed Using a Bedside Hand-Held Device - Mueller, Helge H. O.; Reike, Mareen; Grosse-Holz, Simon; Röther, Mareike; Likke, Caroline; Philipsen, Alexandra; Kornhuber, Johannes; Groemer, Teja W. (Mental Illness, 2017)
Electroconvulsive therapy (ECT) is effective in the treatment of treatment-resistant major depression. The fear of cognitive impairment after ECT often deters patients from choosing this treatment option. There is little reliable information regarding the effects of ECT on overall cognitive performance, while short-term memory deficits are well known but not easy to measure within clinical routines. In this pilot study, we examined ECT recipients' pre- and post-treatment performances on a digital ascending number tapping test. We found that cognitive performance measures exhibited good reproducibility in individual patients and that ECT did not significantly alter cognitive performance up to 2 hours after this therapy was applied. Our results can help patients and physicians make decisions regarding the administration of ECT. Digital measurements are recommended, especially when screening for the most common side effects on cognitive performance and short-term memory.
EVALuna2:33739